Adaptive multi-agents synchronization for collaborative driving of autonomous vehicles with multiple communication delays. (January 2018) - Petrillo, Alberto; Salvi, Alessandro; Santini, Stefania; Valente, Antonio Saverio
Highlights: The cooperative driving problem for autonomous vehicles is addressed. The ensemble of autonomous vehicles is modeled as a multi-agent system. An adaptive collaborative approach to solve the leader tracking problem is proposed. We analytically demonstrate the control stability with a Lyapunov-Krasovskii approach. The effectiveness of the proposed strategy is shown via numerical simulations in Plexe (Platooning extension for Veins). Abstract: The development of automated and coordinated driving systems (platooning) is an hot topic today for vehicles and it represents a challenging scenario that heavily relies on distributed control in the presence of wireless communication network. To actuate platooning in a safe way it is necessary to design controllers able to effectively operate on informations exchanged via Inter-Vehicular Communication (IVC) systems despite the presence of unavoidable communication impairments, such as multiple time-varying delays that affect communication links. To this aim in this paper we propose a novel distributed adaptive collaborative control strategy that exploits information coming from connected vehicles to achieve leader synchronization and we analytically demonstrate its stability with a Lyapunov-Krasovskii approach. The effectiveness of the proposed strategy is shown via numerical simulations in Plexe, a state of the art IVC and mobility simulator that includes basic building blocks for platooning.